A rapid and efficient in vitro regeneration system for lettuce (Lactuca sativa L.) - Isabel Armas; Natalia Pogrebnyak; Ilya Raskin (Plant Methods, 2017)
Abstract Background Successful biotechnological improvement of crop plants requires a reliable and efficient in vitro regeneration system. Lettuce (Lactuca sativa L.), one the most important vegetable crops worldwide, is strongly genotype-dependent in terms of regeneration capacity, limiting the potential for biotechnological improvement of cultivars which show recalcitrance under currently available protocols. The effect of different nutrient sources, plant hormone combinations and activated charcoal supplementation on shoot induction efficiency was evaluated on the cultivar ‘RSL NFR’, which had previously shown poor regeneration efficiency. Results Multiple shoot organogenesis from cotyledon explants was recorded at the highest frequency and speed on Murashige and Skoog regeneration medium supplemented with 200 mg/l of activated charcoal, 3% sucrose, 10 mg/l benzylaminopurine and 0.5 mg/l naphthaleneacetic acid, which induced shoots through direct regeneration in 90.8 ± 7.9% of explants. High shoot induction efficiency was also observed, albeit not quantified, when using this medium on some other cultivars. Conclusions This activated charcoal-containing regeneration medium might offer a rapid and efficient option for direct shoot induction in some lettuce genotypes that do not respond well to common lettuce regeneration protocols. This is also the first report of the effect of activated charcoal in lettuce tissue culture.